2021
DOI: 10.3390/nu13062080
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast Consumption Habits at Age 6 and Cognitive Ability at Age 12: A Longitudinal Cohort Study

Abstract: This study aimed to assess the relationship between breakfast composition and long-term regular breakfast consumption and cognitive function. Participants included 835 children from the China Jintan Cohort Study for the cross-sectional study and 511 children for the longitudinal study. Breakfast consumption was assessed at ages 6 and 12 through parental and self-administered questionnaires. Cognitive ability was measured as a composition of IQ at age 6 and 12 and academic achievement at age 12, which were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…On the contrary, there are some inconsistent reports of associations between dairy intake and executive function ( 19 , 33 ). No association was observed between dairy intake and cognitive ability assessed by the Wechsler Intelligence Scales in a 6-year longitudinal study ( 18 ). Additionally, several studies carried out on older adults suggested that greater dairy intake is related to poorer memory performance and cognitive function ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, there are some inconsistent reports of associations between dairy intake and executive function ( 19 , 33 ). No association was observed between dairy intake and cognitive ability assessed by the Wechsler Intelligence Scales in a 6-year longitudinal study ( 18 ). Additionally, several studies carried out on older adults suggested that greater dairy intake is related to poorer memory performance and cognitive function ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several studies carried out on older adults suggested that greater dairy intake is related to poorer memory performance and cognitive function ( 36 , 37 ). The pieces of literature with these inconsistent conclusions pointed out that the failure to distinguish between high- and low-fat dairy intakes is a possible reason ( 18 , 36 ). Based on the above, the current study explored the role of dairy fat content in this relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study [ 50 ] showed that higher milk consumption could improve overall nutritional status in Korea adolescents, and the well-nourished children often performed better than the malnourished children [ 19 ]. In addition, higher consumption of meat or egg during breakfast might contribute to improved cognitive ability in youth [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanistic pathway through which breakfast enhances cognition could be through the immediate cognitive impact of breakfast consumption. Studies have suggested that breakfasts rich in complex carbohydrates aid cognitive performance throughout the morning, which may be mediated by the glycemic index (GI) or glycemic load (GL) 45 . Recently, a randomeffects meta-analysis model revealed no effect of GL on cognition up to 119 minutes post-consumption.…”
Section: Discussionmentioning
confidence: 99%